2010
DOI: 10.1002/zaac.201000301
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bond‐Based Magnetic Exchange Between μ‐Diethylnicotinamide(aqua)bis(X‐salicylato)copper(II) Polymeric Chains

Abstract: Polymeric salicylatocopper(II) complexes of unusual composition [Cu(X-sal) 2 (μ-denia)(H 2 O)] n [denia = diethylnicotinamide, and X-sal = 5-methylsalicylate (1), 3-methylsalicylate (2), 4-methoxysalicylate (3), 3,5-dichlorosalicylate (4) and 3,5-dibromosalicylate (5)] were synthesized and characterized. Magnetic measurements were performed in the temperature range 1.8-300 K. The structural unit of all complexes consists of a Cu II atom, which is monodentately coordinated by the pair of X-salicylate anions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Exchange interactions through a priori weak supramolecular interactions, such as hydrogen-bond bridges linking metal centers, have been only rarely investigated [7,[23][24][25][26][27][28][29][30][31][32]. It is obvious that the distance between paramagnetic centers is not the only factor influencing the interaction, and the form of magnetic dimensionality could be different from its structural dimensionality [26][27][28]. A theoretical investigation of exchange coupling through hydrogen bonding indicates that hydrogen bonds are responsible for fixing molecules in position allowing overlap of magnetic orbitals [32].…”
Section: Magnetic Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Exchange interactions through a priori weak supramolecular interactions, such as hydrogen-bond bridges linking metal centers, have been only rarely investigated [7,[23][24][25][26][27][28][29][30][31][32]. It is obvious that the distance between paramagnetic centers is not the only factor influencing the interaction, and the form of magnetic dimensionality could be different from its structural dimensionality [26][27][28]. A theoretical investigation of exchange coupling through hydrogen bonding indicates that hydrogen bonds are responsible for fixing molecules in position allowing overlap of magnetic orbitals [32].…”
Section: Magnetic Propertiesmentioning
confidence: 97%
“…Good extrapolation to experimental data has been obtained for both models (see figure 3 and table 3) with a good agreement factor R defined as follows: [22] where magnetic coupling between two copper(II) ions could be caused through water and bpy (Cu⋯O-H⋯C-C-N-Cu). Exchange interactions through a priori weak supramolecular interactions, such as hydrogen-bond bridges linking metal centers, have been only rarely investigated [7,[23][24][25][26][27][28][29][30][31][32]. It is obvious that the distance between paramagnetic centers is not the only factor influencing the interaction, and the form of magnetic dimensionality could be different from its structural dimensionality [26][27][28].…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…3) and c g ···c g distance (Janiak, 2000) is 4.17 Å. The similar supramolecular synthons R 2 2 (10) and R 2 2 (12) (Bernstein et al, 1995) have been also observed in crystal structure of one dinuclear complex (Valigura et al, 2006) and several polymeric complexes (Abourahma et al, 2002;Burrows et al, 2008;Cao et al, 2008;Korabik et al, 2011;Maharramov et al, 2012;Vaskova et al, 2011;Xu et al, 2007;Yamada et al, 1998). The crystal packing of 1 is shown in Fig.…”
Section: Resultsmentioning
confidence: 71%
“…The planning in coordination crystal engineering, construction of the structures of crystalline coordination compounds, [1] depends on a number of experimental variables such as the solvent, time of reaction, reagent ratio, temperature, pH, guest molecules and counterions. In this regard, chemical structure of the organic ligand [2] -eventh slight of the substitute position-and preferred coordination geometry of the metal [3] play an important role on the formation of different molecular architecture of complexes in the assembly processes. To make progress in controlling specific interactions in the solid state of coordination compounds requires systematic investigations of the effects of different factors on the final structures.…”
Section: Influence Of Ligand Substituent On Molecular Architecture; Vmentioning
confidence: 99%
“…Some copper(II) carboxylate complexes have shown that the intermolecular H-bonds can alter their magnetic properties. We have recently published mononuclear molecular complex [1], binuclear molecular complex [2] and more coordination polymers [3,4] which exhibit similar magnetic properties. These very similar magnetic properties of mononuclear, binuclear as well as polymeric complexes could be explained by the presence of very similar H-bond systems, supramolecular synthons, that are pathway for antiferromagnetic interactions.…”
Section: Influence Of Ligand Substituent On Molecular Architecture; Vmentioning
confidence: 99%